SYNTHESIS OF NEW CHIRAL Ni(II) COMPLEXES OF SCHIFF’S BASE OF DEHYDROALANINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
New methods for the synthesis of the chiral reagents (S)-N-(2-benzoylphenyl)-l-(3,4-dichlorbenzyl)pirrolydin-2-carboxamide (CPB) and (S)-N-(2-(2',5'-dimethylphenyl)benzoyl)-1-benzylpirrolydin-2-carboxamide (BBX) and their chiral Ni2+ complexes of Schifts bases with dehydroalanine (Ni-CPB-Δ-Ala and Ni-BBX-Δ-Ala) has been elaborated. All the complexes derived from BBX are formed as atropoisomers. These atropoisomers were isolated and subjected to spectral analysis.
Keywords: S)-N-(2-benzoylphenyl)-l-(3,4-dichlorbenzyl)pirrolydin-2-carboxamide; (S)-N-(2-(2',5'-dimethylphenyl)benzoyl)-1-benzylpirrolydin-2-carboxamide; Schifts bases; atropoisomers